Effect Education of DASH DIET on Dietary Intake Adherence and Blood Pressure of Hypertension Outpatients in Rumkital Marinir Cilandak - Rita Uliatiningsih; Adhila Fayasari (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2019)
Background: Diet DASH (Dietary Approaches To Stop Hypertension) is one of the methods to lowering high blood pressure. Dietary compliance is one of the important things that hypertensive patients need to care of. The hypertensive patients should obey DASH diet in order to avoid further complication. This study aims to discover the effect of DASH diet education on diet adherence and blood preesure re in hypertensive patients in Cilandak Marine Hospital, Jakarta.Method: This study used quasi experimental design with pretest-posttest one group design approaches. There were 75 respondents in this study which were obtained using purposive sampling type. The data were obtained from Cilandak Marine Hospital, Jakarta. The statistical analysis used paired sample t test. Result: The result of the study showed that dietary compliance of DASH diet with blood pressure in hypertensive patients in Cilandak Marine Hospital, Jakarta were categorized 3 parts as non compliants when the score is 31-45 for as many as 32 respondents (42,7%), fair compliants when the score is 46-60 for as many as 39 respondent (52,0%) and 4 respondents (5,3%) are categorized in compliant score 61-75. The analysis of the systole and diastole of the blood pressure before and after the intervention in hypertensive patients showed a significant related correlation (p=0,000) .Conclusion: There is a significant correlation between the dietary compliance of DASH diet with blood pressure in hypertensive patients in Cilandak Marine Hospital, Jakarta.